Contribution of Ameliorant Application on Carbon Balance in Rice (Oryza Sativa L.) Cropping in Peatland - Eni Yulianingsing; HL Susilawati; Prihasto Setyanto (Center for Journal Management and Publication, 2015)
Expansion of agricultural land is needed to accomplish the future national food demand. Expansion of agricultural land has been focused on marginal land such as peatland. The studies was carried out at IAERI experimental farm and used 12 microplots with each have a dimension of 1,5 m x 1,5 m x 1 m and was filled with peat from South Kalimantan. Amelioration treatments such as dolomite (Ca-rock), volcanic ash, peat fertilizer, Fe fertilizer, nitrification inhibitor and control were established as treatments to the microplots, after amelioration, the plots was planted by Inpara 2 rice cultivar. Data of the result was analyzed by Analysis of Variance (ANOVA) and Duncant Multiple Range Test (DMRT). The result showed that the highest net carbon from non ameliorant (control) and the lowest from volcanic ash. Net carbon highet at non ameliorant (control) 3785 kg-C/ha followed dolomite, Fe fertilizer, NI (nitrification inhibitor), peatland fertilizer and volcanic ash i.e 3238; 2082; 1574; 1439 and -712 kg-C/ha